1. Oblicz:
(-1/2)³=
(-0,06)²=
(-1/3)⁴=
(-0,5)³=

2. Wstaw znak <, = lub >:
a) (-5)×(-7,2)×(9 ¾)×6½ .. 0
b) (-7⅓)×(-3,6)×4×(-3,2)××5⅖ .. 5
c) 4⅔×(-6½) ×0×(-2⅔) .. -3
d) (-3½):(-2⅔)
(-3,2)×(-5)×3,72 .. 0
e) (-1)³×(-1)⁴×(-1)⁷.. 1
f) (-12)⁴ ×(-12)⁵ ×(-12)³ .. 0
g) (-2)⁷×(-2)³×(-2)⁵.. 0
h) (-1)⁷: (-1)² .. (-1)⁶÷(-1)³

3. Oblicz jak najprostszym sposobem:
a) ⅜×(-0,9)×(-16/3)×10=
b) 5×(-0,25)×0,2×(-4)=
c) (-2,5)×0,2×(-10)×2=
d) (-6)×(-4/7)×⅖×(-7)×5/12=
e) (-1½)×0,06×(-⅔)×100=

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-15T16:14:10+01:00
1. Oblicz:
(-1/2)³=-1/8
(-0,06)²=0,0036
(-1/3)⁴=1/81
(-0,5)³=-0,125

2. Wstaw znak <, = lub >:
a) (-5)×(-7,2)×(9 ¾)×6½ > 0
b) (-7⅓)×(-3,6)×4×(-3,2)×5⅖ < 5
c) 4⅔×(-6½) ×0×(-2⅔) > -3
d) (-3½):(-2⅔)????????????
(-3,2)×(-5)×3,72 > 0
e) (-1)³×(-1)⁴×(-1)⁷= 1
f) (-12)⁴ ×(-12)⁵ ×(-12)³ > 0
g) (-2)⁷×(-2)³×(-2)⁵< 0
h) (-1)⁷: (-1)² = (-1)⁶÷(-1)³

3. Oblicz jak najprostszym sposobem:
a) ⅜×(-0,9)×(-16/3)×10=(-0,9)*10*3/8*(-16/3)=(-9)*(-2)=18
b) 5×(-0,25)×0,2×(-4)=5*0,2*(-4)*(-0,25)=1
c) (-2,5)×0,2×(-10)×2=(-2,5)*2*0,2*(-10)=(-5)*(-2)=10
d) (-6)×(-4/7)×⅖×(-7)×5/12=(-6)*(-7)*(-4/7)*(2/5)*5/12=42*(-4/7)*1/6=7*(-4/7)=-4
e) (-1½)×0,06×(-⅔)×100=(-1,5)*(-2/5)*0,06*100=6*3/5=18/5=3,6